Optimasi Temperatur dan Persentase Air pada Pregelatinisasi Pati Kacang Hijau (Vigna radiata L.) - Yulanda Fitriana (Fakultas Farmasi, 2026)
Natural excipients, such as starch, are increasingly developed due to their safety and biodegradability, yet native starch often has poor flowability and compressibility. This study aimed to determine the effects of temperature and water percentage on the physical characteristics, specifically angle of repose, compressibility index, and swelling index, of pregelatinized mung bean (Vigna radiata L.) starch and to identify its optimum conditions. Mung bean starch was isolated and modified using the pregelatinization method, involving heating in water followed by drying. The optimization process was conducted using a 2² factorial design, using two independent variables: the pregelatinization temperature (at levels of 50°C and 65°C) and the water percentage (at 50% and 80%) resulting in four combination F(1), F(A), F(B), and F(AB). Data analysis was performed using Design-Expert 13 to evaluate the interactions between these factors on physical properties. The results indicated that increased temperature, higher water percentage, and their interaction significantly influenced the physical characteristics by decreasing the angle of repose and compressibility index while increasing the swelling index. Higher temperatures weakened hydrogen bonds, allowing greater water penetration and granule expansion, which reduced interparticle cohesiveness and improved flow properties. The optimum pregelatinization conditions were found at a temperature of 65°C and a water percentage of 80%. This condition yielded an angle of repose of 29.054°, a compressibility index of 13.852%, and a swelling index of 88.889%. All the obtained values are categorized as "excellent" and "good" categories. In conclusion, pregelatinized mung bean starch produced under these optimum conditions exhibits enhanced flowability, compressibility, and swelling ability, as evidenced by reduction in angle of repose and compressibility index, and also increase its swelling index.
Finalisasi 23 Juli 2026_Yudi
Keywords: Pregelatinisasi pati; pregelatinized mung bean starch; temperature; water percentage